The Image of Women in the Hikayat Perempuan by Amelia Hashim (Malaysia) and Isinga Roman Papua by Dorothea Rosa Herliany (Indonesia) Based on Feminist Critical Theory: [Citra Wanita dalam Hikayat Perempuan oleh Amelia Hashim (Malaysia) dan Isinga: Roman Papua Oleh Dorothea Rosa Herliany (Indonesia) Berdasarkan Teori Kritikan Feminis] (Malay Literature, 2021)
Literary works by male or female authors that lean towards the style of male authors often portray women in stereotypical images, such as the marginalization of women's experiences, the silencing of women's voices, and various displays of male-centredness. This type of writing pattern is an illustration of the continuous oppression of women, and thus reflects the stereotypical traits of women in literature. This paper discusses the novels Hikayat Perempuan from Malaysia and Isinga Roman Papua from Indonesia. The objective of this study is to identify the stereotypical traits of women illustrated in the study texts and analyse the extent to which these stereotypical traits dominate the images of women displayed. The analysis is done using the Feminist critical theory by Elaine Showalter. The finding of this study shows that several stereotypical traits are portrayed by the authors, while the remaining images of women have done away with such stereotypes. This finding proves that not all female authors emulate the style of male authors in displaying stereotypical images of women. Conversely, there are attempts by female authors to abolish some of the said stereotypical traits of women.